Arylglycine-derivative synthesis via oxidative sp3 C–H functionalization of α-amino esters - Xu, Zhanwei; Yu, Xiaoqiang; Feng, Xiujuan; Bao, Ming (Beilstein Journal of Organic Chemistry, 2012)
An efficient method for the synthesis of arylglycine derivatives is described. The oxidative coupling reactions of naphthols and phenols with α-amino esters proceeded smoothly in the presence of meta-chloroperoxybenzoic acid as an oxidant under ambient conditions, to produce arylglycine derivatives in satisfactory yields.
Keywords: α-amino ester; arylglycine; C–H functionalization; oxidation; synthesis